A versatile route to fabricate single atom catalysts with high chemoselectivity and regioselectivity in hydrogenation - Xiaohui He (Nature Portfolio, 2019)
The general synthesis of single atom catalysts (SACs) is of broad interest to chemists but remains a formidable challenge. Here, with the precursor-dilution strategy, the authors successfully prepare 24 different SACs and the Pt SACs exhibit superior chemo- and regio-selectivity in hydrogenation.